The effect of IFSA 2013 on late payment of takāful benefits - Muhammad Ali Jinnah Ahmad (ISRA International Journal of Islamic Finance, 2017)
Purpose: This paper aims to examine the implications of compensation on late payment of takāful benefit imposed in the Islamic Financial Services Act 2013 on the takāful industry in Malaysia. It also aims to identify the issues and challenges faced by takāful operators in the implementation of the compensation and propose solutions for the benefits of the takāful industry. Design/methodology/approach This research uses the qualitative approach to understand the practices of claims in takāful and to analyze the implication of compensation on late payment of takāful benefit to the takāful industry in Malaysia. Data are collected through survey and interview with various takāful stakeholders. Findings Some of the key findings in this research are that the compensation of late payment of takāful benefit has a positive impact to the takāful industry. The research also found some Sharīʿah operational issues in terms of its implementation among takāful operators. Research limitations/implications The research focuses on compensation on late payment of takāful benefit claim in death and personal accident only. Practical implications The research offers certainty to the takāful industry and an explanation to academic and legal fraternities on the implementation of compensation on late payment of takāful benefit according to Islamic Financial Services Act (IFSA) 2013. Originality/value The research provides a valuable contribution to the current practices of takāful operators, identifies some issues and challenges of its implementation and proposes the solution.
Keywords: 330; claim; IFSA 2013; late payment; Takāful benefit